Pectic polysaccharides from Tartary buckwheat sprouts: Effects of ultrasound-assisted Fenton treatment and mild alkali treatment on their physicochemical characteristics and biological functions - Wen-Bing Li; Jin Wang; Mei-Mei Qu Mo; Jie Li; Min Li; Yuan Liu; Shengpeng Wang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Ultrasonics Sonochemistry, 2024)
Buckwheat sprouts are rich in pectic polysaccharides, which possess numerous health-improving benefits. However, the precise structure–activity relationship of pectic polysaccharides from Tartary buckwheat sprouts (TP) is still scant, which ultimately restricts their applications in the food industry. Hence, both ultrasound-assisted Fenton treatment (UAFT) and mild alkali treatment (MATT) were utilized for the modification of TP, and then the effects of physicochemical characteristics of original and modified TPs on their bioactivities were assessed. Our findings reveled that the UAFT treatment could precisely reduce TP’s molecular weight, with the levels decreased from 8.191 × 104 Da to 0.957 × 104 Da. Meanwhile, the MATT treatment could precisely reduce TP’s esterification degree, with the values decreased from 28.04 % to 4.72 %. Nevertheless, both UAFT and MATT treatments had limited effects on the backbone and branched chain of TP. Moreover, our findings unveiled that the UAFT treatment could notably promote TP’s antioxidant, antiglycation, and immunostimulatory effects, while remarkedly reduce TP’s anti-hyperlipidemic effect, which were probably owing to that the UAFT treatment obviously reduced TP’s molecular weight. Additionally, the MATT treatment could also promote TP’s immunostimulatory effect, which was probably attributed to that the MATT treatment significantly decreased TP’s esterification degree. Interestingly, the MATT treatment could regulate TP’s antioxidant and antiglycation effects, which was probably attributed to that the MATT treatment simultaneously reduced its esterification degree and bound phenolics. Our findings are conducive to understanding TP’s structure–activity relationship, and can afford a scientific theoretical basis for the development of functional or healthy products based on TPs. Besides, the UAFT treatment can be a promising approach for the modification of TP to improve its biological functions.